La sociedad civil en Europa Occidental - Giner, Salvador; Moreno, Luis (Estudios Internacionales, 1990)
Western Europe is the cradle of civil society. Owning it is one of its most outstanding historical features. Civil society is that historically constituted sphere of individual rights, freedoms and voluntary associations, whose autonomy and mutual concurrence in the pursuit of their private interests and intentions are guaranteed by the state and the law. This paper explores its origins and then examines several of the most salient dimensions of perceptible socio-structural change in Western European countries in recent decades: social mobility, the new salaried classes, old and new middle classes, upper classes and European elites, to finally analyze the social future of Europe.